2013
DOI: 10.1517/14728222.2014.851671
|View full text |Cite
|
Sign up to set email alerts
|

The role of sphingosine-1 phosphate and ceramide-1 phosphate in trafficking of normal stem cells and cancer cells

Abstract: Introduction A common feature of many types of cells is their responsiveness to chemotactic gradients of factors for which they express the corresponding receptors. The most studied chemoattractants so far are peptide-based growth factors and a family of cytokines endowed with strong chemotactic properties, called chemokines. However, additional evidence has accumulated that, in addition to these peptide-based chemoattractants, an important role in cell migration is played by bioactive lipids. Areas covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 99 publications
(181 reference statements)
1
42
0
Order By: Relevance
“…It was concluded that the C1P receptor could be an important drug target for treatment of illnesses in which macrophage migration is a major cause of pathology, as it occurs in inflammatory responses or tumor metastasis. The chemotactic effects of C1P have been confirmed in different biological systems, including homing of hematopoietic stem/progenitor cells to the bone marrow or multipotent stromal cell and endothelial progenitor cell migration ( (Karapetyan et al 2013;Kim et al 2012;Ratajczak et al 2010). Of interest, it was also observed that S1P and C1P stimulated migration of bone marrow-derived stem cells in patients suffering from acute myocardial infarction.…”
Section: Role Of Ceramide Kinase/c1p In Inflammationmentioning
confidence: 92%
See 1 more Smart Citation
“…It was concluded that the C1P receptor could be an important drug target for treatment of illnesses in which macrophage migration is a major cause of pathology, as it occurs in inflammatory responses or tumor metastasis. The chemotactic effects of C1P have been confirmed in different biological systems, including homing of hematopoietic stem/progenitor cells to the bone marrow or multipotent stromal cell and endothelial progenitor cell migration ( (Karapetyan et al 2013;Kim et al 2012;Ratajczak et al 2010). Of interest, it was also observed that S1P and C1P stimulated migration of bone marrow-derived stem cells in patients suffering from acute myocardial infarction.…”
Section: Role Of Ceramide Kinase/c1p In Inflammationmentioning
confidence: 92%
“…CerK has been also implicated in neuroblastoma cell proliferation, suggesting that inhibition of this enzyme may be a possible target for anticancer therapy of human neuroblastoma (Bini et al 2012). On the other hand, C1P has been demonstrated to mediate inflammatory responses (Chalfant and Spiegel 2005;HinkovskaGalcheva et al 2005) and to promote cell migration Granado et al 2009b;Karapetyan et al 2013;Kim et al 2012;Ratajczak et al 2010), an action that is also associated to inflammation. Utilizing a combination of pharmacological and molecular approaches, Barth and co-coworkers demonstrated that in human neuroblastoma cells, CerK activity was strictly required for activation of various oxidoreductases, including reactive oxygen species (ROS) producing NADPH oxidase (NOX), cyclooxygenase (COX), and 5-lipooxygenase (5-LOX), which are enzymes involved in pro-inflammatory processes (Barth et al 2012).…”
Section: Pathophysiological Relevancementioning
confidence: 99%
“…These include the sphingolipids sphingosine-1-phosphate (S1P) [100,[125][126][127][128] that couple to G protein-coupled sphingosine 1-phosphate receptor 1 (S1P1), and ceramide-1-phosphate (C1P) which acts via an hitherto unknown receptor [127,129]. Moreover, extracellular nucleotides, such as adenosine triphosphate (ATP) or uridine triphosphate (UTP) [130] and divalent cation Ca 2+ and the CaR, and H + [131,132] regulate adhesion molecules on the surface of the HSPCs as well as on certain cells of the stem cell niches.…”
Section: Sphingolipids and Nucleotides In Hspc Mobilizationmentioning
confidence: 99%
“…Both these mechanisms may desensitize responses to potential homing gradients of these bioactive lipids [129].…”
Section: C1pmentioning
confidence: 99%
“…Extracellular S1P regulates proliferation and migration of divers cell types such as vascular cells but also in several tumor types [21] and is a critical regulator of the physiology of the immune and vascular systems, i.e. regulates lymphocyte egress, angiogenesis and platelet maturation and stem cell functions [25,36,37,38]. In addition, recent studies highlight numerous interactions between blood coagulation and the S1P signaling system [18].…”
Section: Introductionmentioning
confidence: 99%